2002
DOI: 10.1034/j.1600-051x.2002.291110.x
|View full text |Cite
|
Sign up to set email alerts
|

A clinical comparison of three powered toothbrushes

Abstract: The data from this study show that the design and action of the Braun Oral-B 3D Excel power toothbrush are more effective in resolving gingivitis than the Sonicare & the Philips Sensiflex 2000 power toothbrushes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…It has been shown that a learning period has an effect with respect to the incidence of gingival abrasion. In a study by Van der Weijden et al (2002) a decrease of 60–75% in incidence of gingival abrasion after 4 weeks of familiarization with powered toothbrushes was found. In the dentifrice experiment the panellists were not allowed a familiarization period, but were entered immediately into the experiment without further previous training.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that a learning period has an effect with respect to the incidence of gingival abrasion. In a study by Van der Weijden et al (2002) a decrease of 60–75% in incidence of gingival abrasion after 4 weeks of familiarization with powered toothbrushes was found. In the dentifrice experiment the panellists were not allowed a familiarization period, but were entered immediately into the experiment without further previous training.…”
Section: Discussionmentioning
confidence: 97%
“…Studies 6–13 over the past decade showed that certain powered toothbrushes (e.g., oscillating‐rotating) are effective at plaque removal and reducing the signs of gingival inflammation. They are capable of effectively reestablishing gingival health after a period of experimentally induced inflammation 14–16 …”
mentioning
confidence: 99%
“…The rationale for a professional brushing exercise has been described in previous papers (Barnes et al 1993, Van der Weijden et al 1993a, 1994, 2002, Stoltze & Bay 1994). Briefly, this study model aims to control as many variables as possible, including duration of toothbrushing, manual dexterity, motivation, the frequency of brushing, the novelty effect and the pre‐brushing amount of plaque (Van der Weijden et al 1993a).…”
Section: Discussionmentioning
confidence: 99%
“…This 3D‐action was developed to enhance penetration and removal of plaque from approximal spaces of the dentition. It is at these spaces that electric toothbrushes appear to be particularly effective while these surfaces are predominantly at risk for caries and periodontal disease (Van der Weijden et al 1993b, 2002).…”
mentioning
confidence: 99%